Chelating Ruthenium Phenolate Complexes: Synthesis, General Catalytic Activity, and Applications in Olefin Metathesis Polymerization. Issue 43 (9th September 2014) - Kozłowska, Anna; Dranka, Maciej; Zachara, Janusz; Pump, Eva; Slugovc, Christian; Skowerski, Krzysztof; Grela, Karol
Abstract: Cyclic Ru‐phenolates were synthesized, and these compounds were used as olefin metathesis catalysts. Investigation of their catalytic activity pointed out that, after activation with chemical agents, these catalysts promote ring‐closing metathesis (RCM), enyne and cross‐metathesis (CM) reactions, including butenolysis, with good results. Importantly, these latent catalysts are soluble in neat dicyclopentadiene (DCPD) and show good applicability in ring‐opening metathesis polymeriyation (ROMP) of this monomer. Abstract : Olefin metathesis catalysis : Investigation of the catalytic activity of Ru phenolate catalysts pointed out that, after activation with chemical agents, these catalysts promote ring‐closing metathesis (RCM), enyne, and cross‐metathesis (CM) reactions, including butenolysis, with good results (see scheme, Mes=2, 4, 6‐trimethylphenyl, Cy=cyclohexyl). The phenolanate catalysts, well soluble in dicyclopentadiene (DCPD), also show good applicability in ring‐opening metathesis polymerization (ROMP) of this monomer.